Ethanol purification using membrane technology - Huang, Ting-Yi (Nanyang Technological University, 2022)
The rapid depletion of non-renewable energy such as fossil fuels has prompted the search for alternative cleaner energy resources in order to meet the world’s rising energy demand and reduce greenhouse gas emissions. Bioethanol has been actively studied in recent years as one of the potential substitutes for fossil fuels. It can be derived from plants through fermentation. To date, conventional distillation is the most practiced technology for ethanol purification due to its high energy efficiency at moderate ethanol concentration. However, it becomes significantly more energy intensive as ethanol concentration falls below 5 wt%. Membrane processes are generally considered to be more selective and less energy intensive owing to their high surface area available for mass and heat transfer. Therefore, by developing a low energy membrane process that can potentially replace distillation for ethanol pre-concentration, energy consumption can be reduced significantly. The first part of this thesis focused on developing a low-energy purification process for ethanol extraction from dilute aqueous solution (2 wt% ethanol in water) by integrating supported ionic liquid membrane (SILM) with perstraction. Preliminary screening tests were performed for the selection of a suitable ionic liquid (IL) and membrane support from three trihexyl(tetradecyl)phosphonium ionic liquids (THTDP) ILs and three commercial polymeric flat-sheet membranes. The optimized combination of solvent and membrane was assessed in a perstraction system. At a feed concentration of 2 wt% ethanol, the selected SILM was able to maintain its functionality for ~240 hours without observable phase intermixing. Despite being subjected to constant lateral shear on the aqueous side, the SILM retained its integrity by maintaining a high ethanol flux of > 2.2 kg/m2 h and selectivity of > 320. Subsequently, the extracted ethanol was recovered from IL by single-stage vacuum-distillation with a final purity of 80% and an overall selectivity of 200. In the second part, two membrane distillation (MD) processes were designed. They include airgap membrane distillation (AGMD) and vacuum membrane distillation (VMD). Parameters including feed temperature, vacuum pressure and feed concentration were varied. Commercial PTFE membranes and in-house modified FAS-coated ceramic membranes were employed. No flux was obtained for all parameters applied in both MD systems due to extensive wetting of the PTFE membranes and ceramic membranes by the IL. Characterization results suggest that the amphiphilic nature of IL results in some chemical affinity with the hydrophobic fluoroalkyl groups in PTFE and FAS coating, which may be the cause of wetting. In the last part, an online detection tool called ultrasonic time-domain reflectometry (UTDR) was employed to study the wetting dynamics of PTFE membranes by THTDP IL. By combining UTDR with offline characterization methods such as contact angle, liquid entry pressure, Fourier-transform infrared spectroscopy and field emission scanning electron microscopy, wetting behavior of the microporous membranes was quantitatively and qualitatively analyzed.